KEPEMIMPINAN SPIRITUAL KEPALA SEKOLAH DALAM MENINGKATKAN KARAKTER PESERTA DIDIK DI SEKOLAH - Mohammad Nurul Huda; Slamet (el Hakim Press, 2023)
Leadership is one of the important things in an educational institution, because a leadership system built by a leader will determine in which direction the educational institution is taken. Spiritual leadership is leadership that brings the worldly dimension to the spiritual dimension (divinity). Like the leadership pattern applied by the Prophet Muhammad SAW, namely the main characteristics including siddiq, amanah, tabligh and fathanah are able to influence others by inspiring without indoctrinating, realizing without hurting, awakening without forcing, and inviting without commanding. The purpose of this study is to describe the principal's spiritual leadership in improving the character of students at the School. The leadership carried out by the principal is to provide understanding, provide examples and examples, familiarize and conduct controls, evaluation. This paper is a type of library research or also called a literature study, because the author collects library data, reads, records and processes from various sources, the main data sources are from books, research results and journals. This paper is expected to provide benefits for observers who are interested in studying the spiritual leadership of school principals in schools